KAJIAN AWAL PEMBUATAN FILM PLASTIK (BAHAN PLASTIK PENGEMAS) DARI PATI BATANG UBI KAYU - Harrison Situmorang, M. Hendra S. Ginting (Universitas Sumatera Utara, 2014)
Starch plastic films made ​​from cassava stem starch by using glycerol as plasticizer and acetic acid as a catalyst gelatinized at 75 °C for 15 minutes. Starch weight, water volume, glycerol volume, and acetic acid volume were varied. The variation conditions of 3 ml of acetic acid volume (3:10 w/w) and 2 ml of glycerol volume (1:4 w/w) gave the best of tensile strength and elongation at break analysis. While at water volume variation, the tensile strength value is inversely proportional to the elongation at break. In FTIR analysis found that α-1,6 glycosidic (1010 cm-1) spectrum disappears as the effect of acetic acid presence, while the spectrum of α-1,4 glycosidic, COH, C=O, and OH shifted as the plasticization effect.